The Image of the Mayors of Valladolid Through Pictures From Diario Regional (Local Newspaper) and Hoja del Lunes (Monday Leaf) (1961-1984) - Sánchez Garre, Nieves; Arráez Betancort, Rosa Mª (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2008)
The pictures of the Mayors that governed during the Late Francoism and the beginning of the democracy between 1961 and 1984, belonging to the fund of the Town Archives of Valladolid, were taken by professionals working for Diario Regional (Local Newspaper) and Hoja del Lunes (Monday Leaf). In the recent article, an analysis based on photographic documents is done in order to construct the image of the Town Councillors deepening into the history of the town and its celebrities, the press and the photography. The archives of photographic documents contribute in the creation of stories that shape the imaginary image of a society. In these documents the official character of the pictures is maintained during all the mandates due to the fact that in Valladolid the change initiated on national level in the middle of the sixties is hardly noticed.